Pengembangan Handout Bergambar disertai Peta Konsep pada Materi Kingdom Plantae untuk Siswa SMA Kelas X Semester II Kurikulum 2006 - Wati, Nila Kusuma; Sumarmin, Ramadhan; Fadilah, Muhyiatul (STKIP PGRI Sumbar, 2013)
ABSTRAK The limited number and kind of learning material in the school will disturb learning process. For that, we must develope learning material. Based on the problem, we do the research to get the result like drawing handout and mind map in Plantae Kingdom material that valid and practice for students in class X Senior High School of even semester 2006 curriculum. This research is developing research with procedural model to result a product. This product developed by three stage from Four-D model, that is; define, design and develop stages. The subjects of this research are five validators, two teachers and twenty students in XI-IA1 from SMAN 2 Lengayang. The data is primary data analyzed descriptively. The result is shows handout with mind map in Plantae Kingdom topic for students in class X of Senior High School even semester 2006 curriculum. Handout is categorized valid by validator with 85,58% value and it categorized to very practice by teachers with 93,47%, practice by students with 86,95%. It can be concludec that handout suplement on the picture with mind map in Plantae Kingdom topic for students in X class of Senior High School even semeser 2006 curriculum is valid and very practice.